2010
DOI: 10.2147/prbm.s7935
|View full text |Cite
|
Sign up to set email alerts
|

Intuition, insight, and the right hemisphere: Emergence of higher sociocognitive functions

Abstract: Intuition is the ability to understand immediately without conscious reasoning and is sometimes explained as a ‘gut feeling’ about the rightness or wrongness of a person, place, situation, temporal episode or object. In contrast, insight is the capacity to gain accurate and a deep understanding of a problem and it is often associated with movement beyond existing paradigms. Examples include Darwin, Einstein and Freud’s theories of natural selection, relativity, or the unconscious; respectively. Many cultures n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 239 publications
(359 reference statements)
1
10
0
2
Order By: Relevance
“…This possibility was also consistent with, for example, Taylor and colleague's study that found the anterior insula was co-activated with the anterior cingulate cortex (ACC) to form an essential part of the salience network, which detected salient events and initiated appropriate control signals to regulate behavior and the homeostatic state (Taylor et al, 2009). It was also generally consistent with the findings of previous neuroimaging studies, which suggested that the anterior insular cortex was involved in cognitive control (Wager and Feldman Barrett, 2004;Ochsner and Gross, 2008;Aziz-Zadeh et al, 2009;McCrea, 2010) given the obvious need for executive functions, such as working memory capacity, inhibition, and category shift in emotion regulation, and the fact that the cognitive reappraisals have to be sustained against competing bias (Schmeichel et al, 2008;Gyurak et al, 2012). In summary, we compared the involvement of the posterior and anterior insular cortex in processing negative stimuli before and after cognitive reappraisal regulation and found that reappraisal could alter the internal bodily and emotional feeling representation in the insular cortex in a posterior-toanterior progression manner.…”
Section: Right Mid-pisupporting
confidence: 89%
“…This possibility was also consistent with, for example, Taylor and colleague's study that found the anterior insula was co-activated with the anterior cingulate cortex (ACC) to form an essential part of the salience network, which detected salient events and initiated appropriate control signals to regulate behavior and the homeostatic state (Taylor et al, 2009). It was also generally consistent with the findings of previous neuroimaging studies, which suggested that the anterior insular cortex was involved in cognitive control (Wager and Feldman Barrett, 2004;Ochsner and Gross, 2008;Aziz-Zadeh et al, 2009;McCrea, 2010) given the obvious need for executive functions, such as working memory capacity, inhibition, and category shift in emotion regulation, and the fact that the cognitive reappraisals have to be sustained against competing bias (Schmeichel et al, 2008;Gyurak et al, 2012). In summary, we compared the involvement of the posterior and anterior insular cortex in processing negative stimuli before and after cognitive reappraisal regulation and found that reappraisal could alter the internal bodily and emotional feeling representation in the insular cortex in a posterior-toanterior progression manner.…”
Section: Right Mid-pisupporting
confidence: 89%
“…The insula may also be linked with the "Aha!" experience [74], but it requires further investigation.…”
Section: Insula and Cerebellummentioning
confidence: 98%
“…As the thalamus is important for transmitting information throughout the entire cortex (Sherman & Guillery, ), it is interesting that strengthened left and right thalamic connectivity was localized to right sensorimotor regions. Though a clear behavioral role for each hemisphere is inconclusive (i.e., right vs. left brain dominance) (Corballis, ), there is accumulating evidence that the right hemisphere is particularly involved in intuition and “insight‐based” functions (McCrea, ), which are highly related to implicit learning in general (Lieberman, ). Though cognitive‐based measures of intuition were not obtained, many nonverbal coding skills (e.g., processing the tone of a voice) have been shown to rely heavily on networks and associated neural substrates primarily within the right hemisphere (Borod, ; Lieberman, ; McCrea, ).…”
Section: Discussionmentioning
confidence: 99%
“…Though a clear behavioral role for each hemisphere is inconclusive (i.e., right vs. left brain dominance) (Corballis, ), there is accumulating evidence that the right hemisphere is particularly involved in intuition and “insight‐based” functions (McCrea, ), which are highly related to implicit learning in general (Lieberman, ). Though cognitive‐based measures of intuition were not obtained, many nonverbal coding skills (e.g., processing the tone of a voice) have been shown to rely heavily on networks and associated neural substrates primarily within the right hemisphere (Borod, ; Lieberman, ; McCrea, ). aNMT abstractly displays information that an athlete must use to learn how to coordinate multiple biomechanics variables without explicit instruction (Bonnette, DiCesare, Kiefer, et al, ; Bonnette et al, ).…”
Section: Discussionmentioning
confidence: 99%